Strategies for Increasing Investment in the Textile Sector through Strengthening the Upstream Industry and Managing Local Raw Materials - Sutjiatmo, Bayu Prabowo; Tyasti, Avia Enggar; Febrianto, Dedi (ADMAN: Journal of Contemporary Administration and Management, 2025)
The textile industry is one of the strategic sectors in Indonesia's economy, with great potential to attract investment. However, the dependency on imported raw materials has become a major obstacle in enhancing the competitiveness of this industry. This study aims to analyze strategies for increasing investment in the textile sector through strengthening the upstream industry and managing local raw materials. The research method used is a literature review with a qualitative approach and descriptive analysis, utilizing data from Google Scholar from 2012 to 2025. Out of 30 initial articles found, only 17 were selected based on strict criteria. The findings show that strengthening the upstream industry through increased local raw material production, the development of alternative fiber innovations, and the implementation of investment incentive policies can enhance the self-sufficiency of the textile sector and reduce dependency on imports. Various case studies discussed show that investment in research and development (R&D), the development of textile industrial zones, and the implementation of a circular economy can improve production efficiency and global competitiveness. The implications of this study include the enhancement of national textile industry resilience, job creation, and strengthening sustainable policies in managing local raw materials. Therefore, support from the government, industry players, and academics is needed to implement appropriate strategies to strengthen the upstream industry and attract investment in the textile sector.